EPCT-21. NEXT-GENERATION SEQUENCING OF CEREBROSPINAL FLUID FOR CLINICAL MOLECULAR DIAGNOSTICS IN ADOLESCENT AND YOUNG ADULT (AYA) BRAIN TUMOR PATIENTS. (1st June 2021) - Miller, Alexandra; Szalontay, Luca; Bouvier, Nancy; Ahmed, Hamza; Hill, Katherine; Rafailov, Johnathan; Lee, Alex; Rodriguez-Sanchez, Irene; Yildirim, Onur; Patel, Arti; Bale, Tejus; Benayed, Ryma; et al.
Abstract: Purpose: Pediatric central nervous system tumors remain a leading cause of cancer-related death in children and adolescents. Safe sampling of tumor tissue for diagnostic purposes may be challenging. Subclinical detection of disease prior to clinical or imaging progression may provide opportunity for earlier intervention and ultimately improve overall survival. Additionally, our understanding of molecular evolution in response to therapy remains limited, given the rarity of serial sampling of tumor tissue. Methods: We report our experience with minimally invasive molecular diagnostics using a validated next generation sequencing assay for sequencing of cerebrospinal fluid (CSF) cell-free DNA (cfDNA) obtained at the time of surgery, by intraventricular catheter or lumbar puncture. All CSF samples were collected as part of clinical care, and results reported to both clinicians and patients/families. Results: We analyzed 64 CSF samples from 45 pediatric and adolescent and young adult (AYA) patients (pediatric=25; AYA=20) with primary and recurrent brain tumors across 12 histopathological subtypes including high-grade glioma (n=10), medulloblastoma (n=10), pineoblastoma (n=5), low grade glioma (n=4), diffuse leptomeningeal glioneuronal tumor (DLGNT) (n=4), metastatic retinoblastoma (n=4), ependymoma (n=3), and other (n=5). Somatic alterations were detected in 28/64 samples (44.4%) and in at least one sample per unique patient in 22/45 patients (48.8%). CSF cfDNA positivity was strongly associated with the presence of disseminated disease at the time of collection (86.3%). No association was seen between CSF cfDNA positivity and the timing of CSF collection during the patient's disease course. Conclusion: We identified four general categories where CSF cfDNA testing provided additional relevant diagnostic, prognostic, and/or therapeutic information, impacting clinical assessment and decision making: 1) diagnosis; 2) identification of actionable alterations; 3) track response to therapy; and 4) monitoring tumor evolution. Our findings support broader implementation of clinical CSF cfDNA testing in this population that may improve care.